Tom Clancy : flash point - Bentley, Don (New York : Berkley, 2024)
"When a benign surveillance operation leads to a crippling attack, Jack Ryan, Jr., finds himself the de facto leader of the Campus team. If there's one thing his father taught him, it's that freedom isn't free, but nothing can prepare Jack for the price he must pay..."--Back cover.
Keywords: Ryan, Jack, -- Jr. (Fictitious character) -- Fiction; Intelligence officers -- Fiction; Conspiracies -- Fiction; Terrorism -- Fiction; South China Sea -- Fiction; Thrillers (Fiction).; Action and adventure fiction; Spy fiction